Effect of Shenfu Injection on Isolated Empty Beating Hearts from Miniature Pigs - Shijie Yin; Zhiqiang Feng; Ansheng Mo; Yi Ding; Jun Wu (Brazilian Journal of Cardiovascular Surgery)
Abstract Objective: To investigate the effect of Shenfu (SF) injection on donor heart preservation. Methods: Twelve pigs were randomly divided into SF group (n=6) and control group (n=6). After eight hours of perfusion, the differences in hemoglobin, the expression of Bcl-2 and BAX, and changes in the myocardial ultrastructure were compared to illustrate the effects of SF injection in heart preservation. Results: The differences in free hemoglobin between the SF group and the control group were statistically significant (P=0.001), and there was significant interaction of groups with times (P=0.019), but the perfusion time may not be associated with the hemoglobin concentration (P=0.616). According to Western blotting analysis, the expression of Bcl-2 was higher in the SF group than in the control group, while the expression of BAX was not different between the two groups. As to ultrastructural changes, both groups exhibited mitochondrial swelling and myofilament lysis, but the degree of damage in the SF group was smaller. Conclusion: Our study suggests that the application of SF injection for heart preservation may protect against cardiomyocytes and erythrocytes apoptosis, and Bcl-2 protein may play a role in these physiological processes.